2010
DOI: 10.1186/1471-2458-10-378
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of human papillomavirus infection and its prevention among adolescents and parents in the greater Milan area, Northern Italy

Abstract: BackgroundIn order to be widely accepted by users, the implementation of a new health intervention requires them to be adequately informed about its clinical importance, benefits and risks. The aim of this study was to provide data on the knowledge of Italian adolescents and parents concerning human papillomavirus (HPV) infection and its prevention in order to allow the development of adequate training programmes.MethodsBetween 2 May and 15 June 2008, we made a cross-sectional survey of 863 high school student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 44 publications
1
84
1
10
Order By: Relevance
“…Compared to one Honduran study (Perkins et al, 2012) and one German study (Kuznetsov et al, 2012) where 22% and 29% of fathers, respectively, had heard of HPV, awareness in this study was slightly higher at 37%, but considerably lower than a recent Italian study where 77% of fathers had heard of HPV (Pelucchi et al, 2010). Higher education level in the Italian study is suggested to be one of the reasons for the difference.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Compared to one Honduran study (Perkins et al, 2012) and one German study (Kuznetsov et al, 2012) where 22% and 29% of fathers, respectively, had heard of HPV, awareness in this study was slightly higher at 37%, but considerably lower than a recent Italian study where 77% of fathers had heard of HPV (Pelucchi et al, 2010). Higher education level in the Italian study is suggested to be one of the reasons for the difference.…”
Section: Discussioncontrasting
confidence: 45%
“…It was also similar to fathers in Honduras (94%) (Perkins et al, 2012) and considerably higher (65%) than the Italian study (Pelucchi et al, 2010), indicating that father's awareness of HPV is not a measure of HPV vaccine acceptance. While all single fathers in both the present and Honduran study indicated they would vaccinate their daughter against HPV, our study did highlight some issues specific to these fathers, such as talking about the sexual nature of HPV or place of vaccination, that need to be addressed.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, 43.5% of adolescent girls wished to be vaccinated against HPV. Similarly, the rate of willingness to be vaccinated varies in a wide range in the literature, notably 48% (Wong et al, 2010), 49% (Mortensen ., 2010), 60.2% (Zimet et al, 2010), 68% (Pelucchi et al, 2010), and 81.7% (Di Giuseppe et al, 2008). In this study, the fact that approximately half of the girls wished to be vaccinated against HPV although none of them had been vaccinated suggests that adolescents girls are ready for vaccination.…”
Section: Discussionmentioning
confidence: 78%
“…Knowledge on HPV vaccines has been reported to be a significant factor affecting the decision for vaccination. On the other hand, the individual's finding herself at risk for HPV infection and related diseases is also an important factor affecting the decision for vaccination (Fazekas et al, 2008;Bendik et al, 2011;Pelucchi et al, 2010). In this study, 21.3% of adolescent girls did not wish to be vaccinated against HPV as they did not find themselves at risk.…”
Section: Discussionmentioning
confidence: 83%
“…Un bajo nivel de conocimientos, combinado con una baja percepción del riesgo de contraer la infección por el VPH incrementa la probabilidad de contagio (19) . Por lo tanto, un primer paso para la modificar los comportamientos de riesgo es lograr que las personas reconozcan la existencia de la infección por el VPH e incrementen su percepción de riesgo de adquisición (13,14,23) , un paso siguiente es lograr que las personas utilicen los servicios de salud para el diagnóstico, tratamiento y seguimiento de los daños producidos por la evolución del VPH (12)(13)(14)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) .…”
Section: Introductionunclassified